2004
DOI: 10.1002/zaac.200400049
|View full text |Cite
|
Sign up to set email alerts
|

Synthesen und Kristallstrukturen von Cu‐ und Ag‐Komplexen mit Dithiophosphinat‐ und Trithiophosphonat‐Liganden

Abstract: Durch Reaktionen von CuI‐ und AgI‐Salzen mit Diphenyldithiophosphinsäuretrimethylsilylester in Gegenwart von tertiären Phosphanen erhält man die Komplexe [Cu(μ‐S)SPPh2(PR3)]2 (R = Me 1a, iPr 1b), [Ag(μ‐S)SPPh2(PnPr3)]2 (2), [Ag(S2PPh2)(PEt3)]2 (3) und [Cu8(μ8‐S)(S2PPh2)6] (4). Bei Verwendung von Phenyltrithiophosphonsäuretrimethylsilylester wird die Käfigverbindung [(PhPS3)2Cu4(PMe3)5] (5) gebildet. Die Verbindungen wurden mit Hilfe der Röntgenstrukturanalyse charakterisiert.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 21 publications
1
27
0
Order By: Relevance
“…In [{(IPr)Cu} 3 (μ 3 -S)] + , the steric protection provided by the IPr ligand 9 is such that the copper centers are present in their lowest possible coordination number of two, and the cluster is stable without the bridging ancillary ligands found in all other examples of CuI n (μ n -S)L m clusters. 2 In view of this finding, we investigated whether NHC ligands would allow synthesis and stabilization of the parent Cu 2 (μ 2 -S) cluster, of which there is one example for Cu II (Chart 1) and none for Cu I . 3 a Herein, we describe three synthetic routes devised to provide {(NHC)Cu I } 2 (μ 2 -S) compounds (Chart 2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [{(IPr)Cu} 3 (μ 3 -S)] + , the steric protection provided by the IPr ligand 9 is such that the copper centers are present in their lowest possible coordination number of two, and the cluster is stable without the bridging ancillary ligands found in all other examples of CuI n (μ n -S)L m clusters. 2 In view of this finding, we investigated whether NHC ligands would allow synthesis and stabilization of the parent Cu 2 (μ 2 -S) cluster, of which there is one example for Cu II (Chart 1) and none for Cu I . 3 a Herein, we describe three synthetic routes devised to provide {(NHC)Cu I } 2 (μ 2 -S) compounds (Chart 2).…”
Section: Introductionmentioning
confidence: 99%
“…Among copper( i )–sulfido clusters, for example, copper centers are found in two, three, and/or four-coordinate geometries, with coordination numbers for the sulfido ligands ranging from three to nine. 1 , 2 , 5f – k The size range of these clusters is correspondingly broad, with examples to date spanning Cu 3 (μ 3 -S)L m 2a , b to Cu 136 S 56 L n 5 k (L = ancillary ligand).…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Recent activities in this field made use of silyl esters of diphenylphosphanyldithioic and phenyltrithiophosphonic acid as starting materials for coinage metal clusters. [5] Also the coordination chemistry of other P/S-containing anions, e.g., phosphorodithioato and -selenolato anions [(RO) 2 …”
Section: Introductionmentioning
confidence: 99%
“…There have been numerous examples of high nuclearity transition metal clusters encapsulating S (Allen, 2002). Such SM 6 clusters have been reported for Fe (Zhang et al, 2002(Zhang et al, , 2003(Zhang et al, , 2004Zuo et al, 2003;Osterloh et al, 1999;Ohki et al, 2003), Cu (Wu, et al, 1988;Marsh, 1997;Hu, 2001;Lin et al, 2000a;Chen et al, 2003;Tang et al, 1993), Co (Shu et al, 1991), Zr (Fenske et al, 1991) and Ag (Chen et al, 2004;Lin et al, 1997;Matsumoto et al, 2000;Lin et al, 2000b;Jin et al, 1996), while SM 8 clusters have been reported for Rh (Vidal et al, 1978) and Cu (Lin et al, 1999;Huang et al, 1991;Dehnen & Fenske, 1996, Liu et al, 1995Fenske et al, 2004). With the exception of one report of an SLi 8 cluster (Banister et al, 1988), there has been no report of an SM x cluster involving a non-transition metal.…”
Section: Commentmentioning
confidence: 89%